Heterogeneous vancomycin-intermediate susceptibility in a community-associated methicillin-resistant Staphylococcus aureus epidemic clone, in a case of Infective Endocarditis in Argentina - Vindel Ana; Torres Alicia; Petiti Juan P; Vilaro Mario; Corso Alejandra; Gonzalez Jose; Huerta Vanina; Diaz Elda G; Gonzalez Patricia; Egea Ana L; Lamberghini Ricardo O; Ciarlantini Marcos; et al. (BMC, 2011)
Abstract Background Community-Associated Methicillin Resistant Staphylococcus aureus (CA-MRSA) has traditionally been related to skin and soft tissue infections in healthy young patients. However, it has now emerged as responsible for severe infections worldwide, for which vancomycin is one of the mainstays of treatment. Infective endocarditis (IE) due to CA-MRSA with heterogeneous vancomycin-intermediate susceptibility-(h-VISA) has been recently reported, associated to an epidemic USA 300 CA-MRSA clone. Case Presentation We describe the occurrence of h-VISA phenotype in a case of IE caused by a strain belonging to an epidemic CA-MRSA clone, distinct from USA300, for the first time in Argentina. The isolate h-VISA (SaB2) was recovered from a patient with persistent bacteraemia after a 7-day therapy with vancomycin, which evolved to fatal case of IE complicated with brain abscesses. The initial isolate-(SaB1) was fully vancomycin susceptible (VSSA). Although MRSA SaB2 was vancomycin susceptible (≤2 μg/ml) by MIC (agar and broth dilution, E-test and VITEK 2), a slight increase of MIC values between SaB1 and SaB2 isolates was detected by the four MIC methods, particularly for teicoplanin. Moreover, Sab2 was classified as h-VISA by three different screening methods [MHA5T-screening agar, Macromethod-E-test-(MET) and by GRD E-test] and confirmed by population analysis profile-(PAP). In addition, a significant increase in cell-wall thickness was revealed for SaB2 by electron microscopy. Molecular typing showed that both strains, SaB1 and SaB2, belonged to ST5 lineage, carried SCCmecIV, lacked Panton-Valentine leukocidin-(PVL) genes and had indistinguishable PFGE patterns (subtype I2), thereby confirming their isogenic nature. In addition, they were clonally related to the epidemic CA-MRSA clone (pulsotype I) detected in our country. Conclusions This report demonstrates the ability of this epidemic CA-MRSA clone, disseminated in some regions of Argentina, to produce severe and rapidly fatal infections such as IE, in addition to its ability to acquire low-level vancomycin resistance; for these reasons, it constitutes a new challenge for the Healthcare System of this country.